Shear softening of earth's inner core as indicated by its high poisson ratio and elastic anisotropy - Zhongqing Wu; Wenzhong Wang (Fundamental Research)
Earth's inner core exhibits an unusually high Poisson ratio and noticeable elastic anisotropy. The mechanisms responsible for these features are crucial to understanding the nature of Earth's core. Although different mechanisms have been proposed, few can explain both observations simultaneously. The results of this study indicated that the crystal with noticeable shear softening would have strong anisotropy and an exceptionally high Poisson ratio simultaneously. Body-centered-cubic (bcc) iron exhibits shear instability at inner-core pressures and can be dynamically stabilized by high temperature and the presence of light elements. The bcc-lattice iron alloy could have strong anisotropy and a Poisson ratio of Earth's inner core before shear instability. Identifying which light elements can stabilize the bcc-lattice iron alloy will provide an independent constraint on the chemical composition of the inner core.